2022
DOI: 10.1007/s11104-022-05559-2
|View full text |Cite
|
Sign up to set email alerts
|

A cool spot in a biodiversity hotspot: why do tall Eucalyptus forests in Southwest Australia exhibit low diversity?

Abstract: Background and aims Southwest Australia is a biodiversity hotspot, with greatest plant species diversity on the most severely phosphorus (P)-impoverished soils. Here, non-mycorrhizal species with highly-effective carboxylate-releasing P-acquisition strategies coexist with mycorrhizal species that are less effective at accessing P on these soils. Non-mycorrhizal carboxylate-releasing species facilitate P acquisition of mycorrhizal neighbours that are better defended against pathogens. In the South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…Phenolic compounds in microbial siderophores are also involved in the mobilization and plant uptake of Fe in the rhizosphere (Nuzzo et al, 2018). In addition, grasses secrete phytosiderophores that act as strong chelators of Fe 3+ , triggering the mobilization of Fe (Chen, Wang, & Yeh, 2017;Kobayashi & Nishizawa, 2012), as well as P (Zhou et al, 2022). Vempati et al (1995) observed that Glycine max root exudates reduce Fe 3+ in soil to Fe 2+ , thus increasing Fe availability in the rhizosphere; this reduction was likely caused by phenolics in root exudates, which were oxidized to diquinones.…”
Section: Do Root Exudates Contribute To Uptake Of Metal Nutrients?mentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds in microbial siderophores are also involved in the mobilization and plant uptake of Fe in the rhizosphere (Nuzzo et al, 2018). In addition, grasses secrete phytosiderophores that act as strong chelators of Fe 3+ , triggering the mobilization of Fe (Chen, Wang, & Yeh, 2017;Kobayashi & Nishizawa, 2012), as well as P (Zhou et al, 2022). Vempati et al (1995) observed that Glycine max root exudates reduce Fe 3+ in soil to Fe 2+ , thus increasing Fe availability in the rhizosphere; this reduction was likely caused by phenolics in root exudates, which were oxidized to diquinones.…”
Section: Do Root Exudates Contribute To Uptake Of Metal Nutrients?mentioning
confidence: 99%
“…Phenolic compounds in microbial siderophores are also involved in the mobilization and plant uptake of Fe in the rhizosphere (Nuzzo et al., 2018). In addition, grasses secrete phytosiderophores that act as strong chelators of Fe 3+ , triggering the mobilization of Fe (Chen, Wang, & Yeh, 2017; Kobayashi & Nishizawa, 2012), as well as P (Zhou et al., 2022). Vempati et al.…”
Section: Do Root Exudates Contribute To Uptake Of Metal Nutrients?mentioning
confidence: 99%
“…Hans says, "I gradually realised that the carboxylate-releasing strategy was far more important than I had even dared to believe at the very beginning. To quantify that, we proposed a tool to screen for species with carboxylate-releasing strategies and the leaf [Mn] approach has become an important screening tool for us, both in ecological studies and in screening crop genotypes" (Lambers et al 2015(Lambers et al , 2021Pang et al 2018;White and Neugebauer 2021;Zhou et al 2022). The approach has been used in ecosystems across the world, not least in China (Tian et al 2021;Yu et al 2020;Zhou et al 2021).…”
Section: An Evolving Landscape For Plant and Soil Research -The Persp...mentioning
confidence: 99%
“…In contrast to this expectation, previous studies have not shown a trade‐off between absorptive fine roots and mycorrhizal extraradical hyphae during stand development (Wallander et al., 2010; Wasyliw et al., 2020). However, it should be noted that these two studies did not consider root exudation, which may also play critical roles in nutrient acquisition, especially for mature stands since stand development may induce N and P deficiency (De Schrijver et al., 2012; DeLuca et al., 2002; Zhou et al., 2022). Therefore, more research is needed to fully understand whether and how tree species coordinate diverse nutrient‐acquisition strategies to acclimate to changes in biotic and abiotic conditions during stand development.…”
Section: Introductionmentioning
confidence: 99%